Effectiveness of laughter therapy on anxiety and depression in hospitalized patients: a systematic review and meta-analysis - Joselin V. SOBALVARRO; Gustavo A. PEREIRA; Ana P. DOMINICCI; Genival A. SANTOS-JUNIOR; Jéssica D. SILVA; Marina BAVARESCO; Tiago M. REIS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: To verify the effectiveness of laughter therapy on anxiety and depression in hospitalized patients. Methods: A systematic review of experimental studies and quasi-experimental studies was carried out after being registered in the PROSPERO database (CRD42020138934). The search was performed in September 2022 in PubMed, Web of Science, Lilacs, Cochrane Library and Scopus. Inclusion criteria were: a) hospitalized patients who experienced anxiety or depression and who underwent at least one session of laughter therapy, b) studies with outcomes of laughter therapy on anxiety and depression. The studies were selected in two stages: by reading the titles and abstracts of the studies, and by reading the full papers that met the eligibility criteria. The risk of bias of the studies was assessed using the RoB 2 and ROBINS-I tools. The quality of the evidence synthesis was measured by GRADE. Results: 4,472 studies were found and 15 of them were included. Laughter therapy was shown to be effective in reducing anxiety and depression in both hospitalized children and adults. Ten were randomized controlled trials (nine of them were at high risk of bias) and five were quasi-experimental studies. Meta-analysis showed significant improvement in anxiety (mean difference = -10.55, 95% CI: -19.97, -1.14, p 0.03, I² = 84%) and depression (mean difference = -2.43, 95% CI: -3.63, -1.24, p <0.0001, I² =0%). Conclusion: According to the findings of this study, it was verified that laughter therapy seems to be more effective than standard care for reducing anxiety and depression in hospitalized patients. However, further studies with low risk of bias are required.